Advanced Glycation End Products, Advanced Oxidation Protein Products, and Ferric Reducing Ability of Plasma Are Correlates of Uncontrolled Hypertension in Patients With Type 2 Diabetes - Seyed Arsalan Seyedi; Reihane Qahremani; Samira Amin Afshari; Armin Rajab; Amirhossein Yadegar; Fatemeh Mohammadi; Mostafa Shomalzadeh; Sahar Karimpour Reyhan; Hossein Mirmiranpour; Soghra Rabizadeh; Alireza Esteghamati; Manouchehr Nakhjavani (Journal of Diabetes Research)
Conclusion: Oxidative stress indices are associated with HTN status and correlated with uncontrolled HTN in populations with T2D.